Edible Film Characteristics Due to The Effect Of Plasticizer (Glycerol) and Moringa Leaf Extract on Moringa Leaves Edible Film - Garnida, Yudi; Gozali, Thomas; Nurfirlian, Shanty (Jurnal Kartika Kimia, 2022)
This study aimed to determine the effect of glycerol and moringa leaf extract on the characteristics of the edible film. The benefit of research is to provide scientific information about the manufacture and characteristics of edible films. The results of the research can improve the quality and economy of Moringa leaves. This research consists of the main research. The preliminary study used a factorial randomized block design (RBD) with a factorial pattern (3x3) with three replications. The responses measured in this study were chemical responses and organoleptic responses. The results showed that the ratio of glycerol and moringa leaf extract affected the characteristics of the edible film.